Factors affecting purchase decision by applying green marketing campaign - Ida Ayu Iswari Pidada; Desak Made Febri Purnama Sari; Ni Putu Sinta Febiola Indah Parwati (Journal of Business & Banking, 2022)
This study aims to determine the effect of green brand image, green price, and brand prestige on purchasing decisions for AQUA Returnable Glass Bottle products. This is a quantitative study with the population of casual dining restaurant customers in Badung Regency. They have decided to purchase and consume AQUA Returnable Glass Bottle products. The data were collected by distributing questionnaires and Likert scale. The sample was taken by using a purposive sampling. The data were analyzed using multiple linear regression analysis. The result showed that partially green brand image, green price, and brand prestige have a positive and significant effect on purchasing decisions. Simultaneously, green brand image, green price, and brand prestige have a significant effect on purchasing decisions. The research implication for AQUA is that it is recommended to be able to maintain the image it already has while still applying green marketing as a tool to support product-purchasing decisions. For further research, the researchers should add other variables and indicators such as green products, green advertising, lifestyle, and social influence.